Social Determinants and Risk Factors Associated with Multi-Drug Resistant Tuberculosis Among Tuberculosis Patients in Tamilnadu - A Case-Control Study - S Suganathan Soundararajan; Pavithra GB; Preeti P; Nisha B; Srinivasan Vengadassalapathy; Ruma Dutta; Gomathy Parasuraman (Medsci Publications, 2022)
Introduction: The emergence of Multi-drug Resistant Tuberculosis (MDR- TB) is a challenge for global control and prevention mainly in developing countries. Socio-economic conditions, social vulnerability, and behavioral factors to be considered as risk factors in identifying MDR-TB. The objective of the study was to identify independent risk factors of MDR-TB among Tuberculosis patients. Methods: An unmatched Case-control study was conducted from January 2021 to June 2021 among tuberculosis (TB) patients registered under RNTCP in Kanchipuram district during the study period. 'Cases' were consecutive MDR TB patients aged 15 and older, diagnosed with MDR-TB. 'Controls' were patients aged 15 and older, diagnosed with drug susceptible TB. Data was collected using pretested semi-structured questionnaire with face-to- face interview. Univariate and multi-variate analysis were used to identify associated determinants of MDR-TB. Results: A total of 80 subjects, 20 cases and 60 controls (1:3) were recruited. Mean age of 'cases' was 32±9.3 years, and for controls was 31± 8.3 years. Multiple logistic regression analysis identified five significant risk factors for the occurrence of MDR TB as follows: passive smoking [OR = 8.449, 95% CI (6.791-30.27)], overcrowding [OR= 2.062,95% CI (1.004-4.005)], low socio-economic status [OR=11.362,95% CI (10.312-35.174)] and previous TB treatment [OR =13.72 with 95% CI (8.599-35.118)]. Inadequate ventilation [OR=4.6434(.217-13.906)] Conclusion: To reduce the burden of drug-resistance, these risk factors can be used as screening tool in identifying individuals with MDR-TB in resource limited settings.